Compensation and Work Culture: Impact on Outsourcing Performance - Haeruddin, Haeruddin; Ahmad, Ibrahim; Hendra, Wawan; Jamali, Hisnol (Budapest International Research and Critics University, 2023)
This research aims to investigate the influence of two key factors, namely compensation and work culture. This research uses a quantitative research approach. Study population 81 person. Samples were selected using saturated samples. Data collection uses an online questionnaire with Google from. The research results reveal that compensation has an insignificant effect on outsourcing performance and work culture has a positive and significant effect on outsourcing performance. Competitive compensation is important in retaining outsourcing service providers and is a motivation for outsourcing, but it does not always have a significant impact on their work results. The uniqueness of this finding lies in the emphasis that work culture factors have a greater influence on outsourcing performance than compensation factors. Therefore, companies are expected to consider strengthening a positive work culture as an approach to increasing cooperation with outsourcing service providers.